Enhancing Vocational High School Students’ English-Speaking Skills Through Comic Strips - Abdussafa, Arif; Karim, Sayit Abdul; Matas, Gordan; Radjaban, R. Yohanes (UIBU, 2026)
This mixed-methods study investigated the effectiveness of comic strips in enhancing the English language skills of tenth-grade vocational students at SMKN 1 Tempel, Yogyakarta. Thirty-six students from Class X AKL 2 participated in the study, which integrated quantitative and qualitative approaches. The characteristics of the participants are; they are active registered students, and have willingness to participate in speaking class activities during data gathering. Data were collected through pre-test and post-test speaking assessments to assess pronunciation, vocabulary, grammar, comprehension, and fluency. Participants had chances to utilize the comic strips three times in the practice stage. Meanwhile. semi-structured interviews were conducted with ten students using purposive sampling technique. Furthermore, quantitative data were analyzed using descriptive statistics, and qualitative data used Miles and Huberman’s (1994) interactive model. The quantitative findings revealed a substantial improvement across all speaking components following the comic strip–based instruction. The highest score increased from 88 to 96, and the lowest score rose from 56 to 64. Vocabulary showed the largest gain, followed by notable increases in comprehension and grammar. Fluency and pronunciation initially the weakest aspects also improved, indicating greater confidence and smoother speech supported by the visual prompts. Overall, the class total score increased from 2476 to 2728, demonstrating a clear enhancement in speaking proficiency. Meanwhile, qualitative results showed that students perceived comic strips as engaging, motivating, and easy to understand. Learning motivation, expanding of vocabulary, and students’ engagement in speaking were the main themes addressed by the participants. Moreover, they reported that the visuals, sequential panels, and word balloons helped them absorb the storyline, generate ideas, recall vocabulary, and speak more coherently. The study implies that comic strips are an effective multimodal resource for supporting speaking instruction in EFL vocational settings, offering contextual scaffolding that enhances learner engagement.